PENGARUH KUALITAS SUMBER DAYA MANUSIA,PEMANFAATAN TEKNOLOGI INFORMASI, PENGENDALIAN INTERN AKUNTANSI,DAN PENGAWASAN KEUANGAN DAERAHTERHADAP KEANDALAN LAPORAN KEUANGAN DAERAH PADA SKPD PEMERINTAH KABUPATEN LOMBOK TIMUR - Muhammad Azlan; Titiek Herwanti; Endar Pituringsih (Jurnal Akuntansi Aktual, 2015)
This studyaimed to analyze the influence of the quality of human resources, utilization ofinformation technology, accounting internal control, and financial over sight of there liability oftheregion’s financial statement presentation area onthe SKPD East Lombok regency government. Datais collected using a question naire. Analysis to olusedis multiple linear regression with SPSS 16. Thepopulation in this study is SKPD locatedin East Lombok to taling 30 SKPD and each SKPD representedby three members, namely the secretary/head of division, head of the division of finance, and treasurerasrespondents. The results showed that the variable quality of human resources, information technologyutilization, internal control accounting and financial control regions positive effect on there liability offinancial statement presentation SKPD East Lombok regency government. Implications of the study theoretically usability stand point of  financial reporting quality information, this research may provide insight into the decision use fulness so as to provide an explanatory theory on the concept of  thinkingabout the importance of the quality of the resulting financial statements are implicated in increasing thefinancial accountability of the government. Such understandingis required so that the data presentedin the financial statements to be useful and used as best as possiblef or the user stomaking the rightdecision.Keywords:human resource qualities, information technology utilization, the controlling intern accountancy,local financial monitoring, reliability